Association between serum arsenic levels and gestational diabetes mellitus: A population-based birth cohort study. (April 2018) - Xia, Xun; Liang, Chunmei; Sheng, Jie; Yan, Shuangqin; Huang, Kun; Li, Zhijuan; Pan, Weijun; Tao, Ruiwen; Hao, Jiahu; Zhu, Beibei; Tong, Shilu; Tao, Fangbiao
Abstract: Gestational diabetes mellitus (GDM) is a common obstetric complication with adverse effects on both mothers and their children. Previous studies revealed the link between Arsenic (As) exposure and incidence of diabetes mellitus (DM), but the data on the association between maternal As exposure and GDM is scarce. We examined this association among a population-based birth cohort. As concentrations were determined at multiple time points during pregnancy by ICP-MS. The association between As levels and GDM prevalence was examined using logistic regression model after adjustment for confounders. A total of 419 (12.85%) women were diagnosed with GDM. The incidences of GDM gradually increased with increasing quartiles of As levels with significant trend. As levels were associated with the GDM (95%CI: 1.29–2.43) at only the 4th quartile in the first trimester. After adjustment for maternal age, prepregnancy body mass index (BMI), monthly income, gestational age and parity, the association remains significant (95%CI: 1.22–2.38). Stratified analyses showed the associations were largely limited to normal maternal age (95%CI: 1.19–3.04) and normal weight women (95%CI: 1.18–2.66). Our study showed an association between As and GDM in a birth cohort and explored first trimester may be the critical period for As associated GDM. This association was universal in the general pregnant population of normal age and of normal weight. Graphical abstract: Image 1 Highlights: As exposure is associated with the risk of GDM at early gestational stage. The first trimester may be the critical period for As-associated GDM. The association is universal among pregnant population of normal age and weight. Abstract : Our study showed an association between GDM and As exposure during early pregnancy, which was largely limited to normal maternal age and weight women.